2019
DOI: 10.1108/jhtt-11-2017-0128
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the congestion situation of a restaurant in a theme park using feedback control

Abstract: Purpose This paper aims to examine a congestion situation of a certain type of restaurant in a theme park (Tokyo Disney Resort) by a simulation based on Little’s law, which is a basic principle in Queueing theory. In the restaurant, a guest (customer) lines up to order, pay and receive dishes. A problem is that even when a guest can easily find vacant tables, it takes a long time to receive dishes. Because guests can see there are vacant tables, there are many tweets of complaints. This situation is a factor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Innovation enables new and established firms to gain competitive advantage (Lichtenthaler, 2020). Customers show favorable intentions when they benefit from innovation; a new way of solving existing problems or delivering services (Sakamoto, 2019; Wang, 2019). To have satisfied customers, companies must create and renew their capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Innovation enables new and established firms to gain competitive advantage (Lichtenthaler, 2020). Customers show favorable intentions when they benefit from innovation; a new way of solving existing problems or delivering services (Sakamoto, 2019; Wang, 2019). To have satisfied customers, companies must create and renew their capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have shown that theme parks select locations based on their potential market and accessibility (Clavé, 2007; Liang, 2019). The principles of location selection also vary regionally (Bao, 2015; Sakamoto, 2019). Systematic approaches to location selection and planning have been proposed in Asian contexts (Bao, 2015; M.…”
Section: Multidisciplinary Perspectives On Theme Park Researchmentioning
confidence: 99%
“…However, little information is available regarding how and to what extent precipitation or temperature affects theme park tourism. Accessibility is a core feature of theme park location selection but is interpreted differently across countries; whereas the Asian market relies heavily on public transportation, the American market is more amenable to self-driving (Bao, 2015; Sakamoto, 2019). Future studies should explore diverse modes of transportation and access routes to facilitate theme park development.…”
Section: Conceptualizing Theme Park Tourismmentioning
confidence: 99%
“…Recent studies have shown that perceived innovativeness is more rewarding in encouraging customers' favourable behaviours than perceived improvement. Customers tend to have favourable intentions when evaluating the benefits of the innovation such as solving the existing problems, fulfilling their needs distinctively, or experiencing a way of delivering services that is perceived novel (Skålén et al, 2015;Sakamoto, 2019;Wang, 2019). Customers evaluate the usefulness, meaningfulness and affordability of the offered service before deciding to use it (Ordanini et al, 2014;Skålén et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%